The evolution of aggregate stock ownership - Kristian Rydqvist; Joshua Spizman; Ilya Strebulaev (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
Since World War II, direct stock ownership by households has largely been replaced by indirect stock ownership by financial institutions. We argue that tax policy is the driving force. Using long time-series from eight countries, we show that the fraction of household ownership decreases with measures of the tax benefits of holding stocks inside a pension plan. This finding is important for policy considerations on effective taxation and for financial economics research on the long-term effects of taxation on corporate finance and asset prices.
urn:nbn:de:hebis:30-115342
Keywords: G10; G20; H22; H30; 330; Capital Gains Tax; Income Tax; Stock Ownership; Bond Ownership; Inflation; Bracket Creep; Pension Funds; Privater Haushalt; Kapitalanlage; Aktienmarkt; Kleinaktionäre; Aktienfonds; Pensionskasse; Steuerpolitik; Welt